The Association between 25-Hydroxyvitamin D and Hemoglobin A1c Levels in Patients with Type 2 Diabetes and Stage 1–5 Chronic Kidney Disease - Farshad Kajbaf; Romuald Mentaverri; Momar Diouf; Albert Fournier; Said Kamel; Jean-Daniel Lalau (International Journal of Endocrinology)
Aim. To examine the relationship between plasma 25-hydroxyvitamin D (25(OH)D) levels and blood hemoglobin A1c (HbA1c) levels in diabetic patients at various stages of chronic kidney disease (CKD). Methods. We screened for data collected between 2003 and 2012. The correlation between 25(OH)D and HbA1c levels was studied in patients categorized according to the severity of CKD and their vitamin D status. A multivariate linear regression model was used to determine whether 25(OH)D and HbA1c levels were independently associated after adjustment for a number of covariates (including erythrocyte metformin levels). Results. We identified 542 reports from 245 patients. The mean HbA1c value was 6.7±1.0% in vitamin D sufficiency, 7.3±1.5% in insufficiency, and 8.4±2.0% in deficiency (P<0.0001). There was a negative correlation between 25(OH)D and HbA1c levels for the population as a whole (r=-0.387, P<0.0001) and in the CKD severity subgroups (r=-0.384, P<0.0001 and r=-0.333, P<0.0001 for CKD stages 1–3 and 4-5, resp.). In the multivariate analysis, the 25(OH)D level was the only factor associated with HbA1c (P<0.0001). Conclusion. 25(OH)D levels were negatively correlated with HbA1c levels independently of study covariates.